Exploring non-traditional typography and visual narrative through Ray Bradbury's "Cistern": rationale two-page spread - McMullin, Shae (My University, 2020)
This is a spread that uses expressive typography and visual treatment to help tell the story of "The Cistern" by Ray Bradbury.
Presented in absentia on April 27, 2020 at "Student Research Day" at MacEwan University in Edmonton, Alberta. (Conference cancelled)
Keywords: typography; book design; visual narrative